Storytelling as narrative practice : ethnographic approaches to the tales we tell - Falconi, Elizabeth (Elizabeth A.); Graber, Kathryn E. (Kathryn Elizabeth) (Studies in pragmatics, 2019)
"Telling stories is one of the fundamental things we do as humans. Yet in scholarship, stories considered to be 'traditional', such as myths, folk tales, and epics, have often been analyzed separately from the narratives of personal experience that we all tell on a daily basis. In Storytelling as Narrative Practice, editors Elizabeth Falconi and Kathryn Graber argue that storytelling is best understood by erasing this analytic divide. Chapter authors carefully examine language use in-situ, drawing on in-depth knowledge gained from long-term fieldwork, to present rich and nuanced analyses of storytelling-as-narrative-practice across a diverse range of global contexts. Each chapter takes a holistic ethnographic approach to show the practices, processes and social consequences of telling stories"--